Health-related quality of life in family caregivers of autistic adults - Dückert, Sophia; Bart, Sabine; Gewohn, Petia; König, Hannah; Schöttle, Daniel; Konnopka, Alexander; Rahlff, Pascal; Erik, Frank; Vogeley, Kai; Schulz, Holger; David, Nicole; Peth, Judith (Frontiers in Psychiatry, 2023)
Family members of autistic individuals often provide support for their autistic relative throughout the lifespan which can lead to massive burden themselves. Reduced health-related Quality of Life (HRQoL) in family caregivers is assumed; however, only a handful studies on the HRQoL of family caregivers providing care to adult relatives exist as opposed to autistic children. Thus, the current study aimed to (i) investigate the current state of physical and mental HRQoL of family caregivers of autistic adults compared to the general population, and (ii) examine caregiver-related (e.g., age, subjective caregiver burden) and care recipient-related variables (e.g., symptom severity, utilization of formal services) explaining variance in the caregivers' HRQoL, using bivariate correlational and multiple linear regression analyses. N = 149 family caregivers completed a nationwide online survey, including, for example, the Short-Form Health Survey (SF-8) in order to assess the HRQoL. Family caregivers of autistic adults reported significantly lower physical (M = 46.71, SD = 8.72, Cohen's d = 0.42) and mental HRQoL (M = 40.15, SD = 11.28, Cohen's d = 1.35) compared to the general population. Multiple linear regression with the mental HRQoL as the outcome showed a significant model (F(11, 95) = 5.53, p <.001, adj. R 2 = .32) with increased subjective burden explaining most of the variance in mental HRQoL (ß = .32, GDW = .141, p < .001). Multiple linear regression analysis with the outcome physical HRQoL did not reveal a statistically significant model (F(11,95) = 1.09, p = .38). However, bivariate analyses also showed a positive correlation with the subjective caregiver burden (r = .20, p < .05). Findings highlight the need to consider HRQoL (and caregiver burden) of family caregivers of autistic adults in several healthcare settings to monitor a potential comprised health status in early stages, with the longterm goal to improve family caregivers' HRQoL.